Just exhale: UiTM students have created a new technique to detect diabetes, writes Izwan Ismail - UiTM, Korporat UiTM (Corporate Communications Department, 2016)
Nur Shima Abdul Aziz, 23, lost her aunt to diabetes a few years ago. Some of her family members are also diabetic. Knowing that diabetes is very expensive to treat, Shima and two of her varsity mates, Mohd Amin Khusyairi Othman and Nur AlyaAhmad, embarked on research to come up with a better and more affordable solution.